Pembelajaran Aktif Berbasis Peer Lesson untuk Meningkatkan Motivasi Belajar Akidah Akhlak di MTs Al-Huda - Irma Suryani; Syahran Jailani; Muhammad Fadhil (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This thesis discusses of peer lesson-based active learning in motivating the learning of morals at MTs Al-huda Dendang, Tanjung Jabung Timur regency. Find out how of peer lesson-based active learning in motivating learning morality at MTs Al-huda Dendang and to find out the supporting and inhibiting factors active learning based on peer lesson in motivating learning morality in MTs Al-huda Dendang, east Tanjung Jabung Timur regency, Jambi Province. This research is a qualitative research is done by using interview, observation, and documentation techniques. The result is that of peer lesson-based active learning is one way to teach students to understand the material from their peers so that they can increase students’ self-confidence to be active in learning which ultimately result in maximum learning success. And the supporting factors for of active learning based on peer lesson in motivating the learning of morality, namely the teacher’s ability to guide students to be more active and creative, guiding students to get used to developing courage in asking questions and opinions. As for the inhibiting factors, such as students still having difficulty understand and remembering the material taught by their friends, overall students are less active in participating in morals learning activities, and difficulties in setting the time for learning activities.